From the history of the socio-material situation of the population of Uzbekistan (on the example of 1920-1940) - Аҳмедова Рашида Муқимовна (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article analyzes the general social and material situation of the population of Uzbekistan for the 1920s and 1940s, the policy pursued by the former Soviet government in the country during this period and the serious material situation of the population, the circumstances of death and several similar circumstances as a result of this policy.